Assessing the Potential for Social Media Activity on the Business-to-Business Service Industry in the United Kingdom: A Research Project for RWB Chartered Accountants, Nottingham - Crowe, James (2012)
This project was carried out with one main goal in mind, which was to investigate the potential of social media activity in the future on the part of RWB Chartered Accountants in Nottingham. The study aimed to understand and predict the best uses and purposes of communicating in the business-to-business service industry via social media. Vital reading was carried out providing a comprehensive review of customer satisfaction, branding, service quality, and client retention literature. This led to a number of key research questions. The project hypothesised that social media activity on the part of RWB Chartered Accountants in Nottingham would be positive, improving service quality and increasing customer satisfaction. Through the use of an e-questionnaire posed to the clients of RWB Chartered Accountants, this project also investigated the potential of social media to assist with cross-selling, improving client retention, and communication of complaints. The research was conclusive and the results disproved the main hypothesis. Indeed the project revealed that social media would not function as a particularly appropriate business tool, nor form of communication with clients, for a company in the situation of RWB Chartered Accountants.